Candide and other stories - Voltaire, 1694-1778 (Oxford world's classics (Oxford University Press), 2006)
Candide is the most famous of Voltaire's 'philosophical tales', in which he combined witty improbabilities with the sanest of good sense. This edition includes four other prose tales - Micromegas, Zadig, The Ing--ecirc--;nu, and The White Bull - and a verse tale based on Chaucer's The Wife of Bath's Tale, : What Pleases the Ladies. - ;'If this is the best of all possible worlds, then what must the others be like?'. Young Candide is tossed on a hilarious tide of misfortune, experiencing the full horror and injustice of this 'best of all possible worlds' - the Old and the New - before finally acc.